Exon skip‐inducing variants in FLNA in an attenuated form of frontometaphyseal dysplasia. Issue 12 (17th July 2021) - Wade, Emma M.; Jenkins, Zandra A.; Morgan, Tim; Gimenez, Gregory; Gibson, Hayley; Peng, Hui; Sanchez Russo, Rossana; Skraban, Cara M.; Bedoukian, Emma; Robertson, Stephen P.
Abstract: Pathogenic variation in the X‐linked gene FLNA causes a wide range of human developmental phenotypes. Loss‐of‐function is usually male embryonic‐lethal, and most commonly results in a neuronal migration disorder in affected females. Gain‐of‐function variants cause a spectrum of skeletal dysplasias that present with variable additional, often distinctive, soft‐tissue anomalies in males and females. Here we present two, unrelated, male individuals with novel, intronic variants in FLNA that are predicted to be pathogenic. Their phenotypes are reminiscent of the gain‐of‐function spectrum without the skeletal manifestations. Most strikingly, they manifest urethral anomalies, cardiac malformations, and keloid scarring, all commonly encountered features of frontometaphyseal dysplasia. Both variants prevent inclusion of exon 40 into the FLNA transcript, predicting the in‐frame deletion of 42 amino acids, however the abundance of FLNA protein was equivalent to that observed in healthy individuals. Loss of these 42 amino acids removes sites that mediate key FLNA functions, including binding of some ligands and phosphorylation. This phenotype further expands the spectrum of the FLNA filaminopathies.